Taxonomic notes on some East Asian pteridophytes - Wan, Xia; Knapp, Ralf; Chen, De-Kui; He, Hai; Zhang, Li-Bing; Hai, Do Van; Thuy, Nguyen Thu; Lin, Zheli; Deng, Yunfei (Phytotaxa, 2023)
Following results of recent studies, Huperzia myriophyllifolia (Huperziaceae), Lycopodium subinundatum (Lycopodiaceae), and Polystichum pseudodeltodon, P. pseudostenophyllum, P. subapiciflorum, and P. subobliquum (Dryopteridaceae) are recognized/reinstated. A new combination, Pseudolycopodiella subinundata, is made based on L. subinundatum. Spinulum lioui (Lycopodiaceae) is reported as a new record for most part of China and other Asian countries.